What are the character values contained in martial arts and how are they integrated into Character Education? Literature review - Albadi Sinulingga; Vicki Ahmad Karisman; Y Touvan Juni Samodra; Didi Suryadi; Isti Dwi Puspita Wati; Asry Syam; Syahruddin Syahruddin; I Gusti Putu Ngurah Adi Santika; Witri Suwanto; Rezza Dewintha (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Character education is not easy to do in the world of education. Need a good synergy between a series of ongoing learning. Especially with sports specifically taking a role in character education efforts. To achieve physical education by using sports, one part of sports is martial arts. This research departs from the idea that martial arts training provides an opportunity to teach character with the value of traditions and activities contained therein. With different activities and customs from several martial arts and lasting for a long time will form habits (including character values) to behave as designed. The research was conducted using literature review. Data base searching used by Scopus and then analysed with PRISMA Steps. The search was conducted in Scopus using the keywords "value AND education AND in AND martial AND arts", "discipline AND education AND in AND martial AND arts and "the AND value AND of AND discipline AND in AND martial AND arts". After reviewing based on PRISMA steps, 17 relevant articles were obtained. Based on the analysis conducted, there are character values in martial arts (Silat, Tae Kwon do, karate, Judo, Wushu, MMA, Wrestling). Both internalization processes occur through continuous habituation with cultural customs that are unique to each branch of martial arts. The cultivation of character values is also influenced by the quality of the trainers as well as the mastery of character, techniques, and tactics in the martial arts. It is important to note that character education through martial arts is very effective and must be well designed, including in routine activities, ceremonies, exercises, and levels. This process needs to be familiarized and guided by experts who understand cultural techniques and tactics.